cis-acting elements involved in photoregulation of an oat phytochrome promoter in rice. - Bruce, W B (1990)
Phytochrome negatively regulates the transcription of its own phyA genes. High levels of Pfr, the active, far-red-light absorbing form of phytochrome, repress phyA transcription; low Pfr levels result in derepression. We have utilized microprojectile-mediated gene transfer to identify regions of an oat phyA3 gene involved in this autoregulation. Chimeric constructs containing various deletion and sequence substitution mutants of the oat phyA3 gene fused to a chloramphenicol acetyltransferase reporter (phyA3/CAT) have been introduced into etiolated rice seedlings by particle bombardment. Low Pfr concentrations induce high phyA3/CAT expression, whereas high Pfr represses activity to near basal levels. Removal of phyA3 sequences 3' to the transcription start site reduces expression about fivefold, suggesting that intron 1 of the phyA3 gene may be required for high activity. The degree of high-Pfr-imposed repression is unaffected by any of a series of deletions or sequence substitutions in the phyA3 promoter, thus providing no evidence of any Pfr-activated negative elements. In contrast, 5' and internal deletions identify a minimum of three major positive promoter elements, designated PE1 [-381 base pairs (bp) to -348 bp], PE2 (-635 bp to -489 bp), and PE3 (-110 bp to -76 bp) that are necessary for high-level expression in low-Pfr cells. The data indicate that PE1 and PE2 are functionally redundant, but that PE3 is required in conjunction with either PE1 or PE2 for activity. PE3 contains a sequence element that is highly conserved between monocot phyA promoters, indicative of a critical role in phyA expression.